Effect of Nano TiO2 Filler Addition on Mechanical Properties of Bamboo/Polyester Hybrid Composites and Parameters Optimized Using Grey Taguchi Method - L. Natrayan; P. V. Arul Kumar; S. Baskara Sethupathy; S. Sekar; Pravin P. Patil; G. Velmurugan; Subash Thanappan (Adsorption Science & Technology)
Exploration has shifted from traditional materials and alloys to composite materials in recent years to develop lightweight, high-effective materials for specific purposes. Natural fibres are less costly, biodegradable, and nonflammable than glass fibres. This study explores how titanium oxide affects woven polyester reinforced composite’s mechanical and physical characteristics. Nanocomposites were created by hand utilizing the following terms: (i) TiO2 nanoparticle filler weight ratio, (ii) fibre content, and (iii) fibre diameter, all at three unique levels. Using the L9 (33) orthogonal design, nine composite samples are generated and tested according to the ASTM standard. According to the research, hybrid composites containing 4% titanium oxide powder and 15 mm length of bamboo fibre with 0.24 mm of bamboo fibre diameter have high mechanical strength. Adding fibre to pristine polyester increased its mechanical properties. As the fibre and filler percentages grew, more effort was required to break the fragments between the matrix and its resin. The verification test, which uses the optimal processing value and grey relational analysis, outperforms the real test results by a wide margin. Tensile strength increased by 14.76%, flexural strength increased by 14.07%, and hardness increased by 25.55%.